Immune cells within the tumor microenvironment: Biological functions and roles in cancer immunotherapy - Lei, Xu; Lei, Yu; Li, Jin-Ke; Du, Wei-Xing; Li, Ru-Gui; Yang, Jing; Li, Jian; Li, Fang; Tan, Hua-Bing (Cancer letters, 2020)
The immune cells within the tumor microenvironment (TME) play important roles in tumorigenesis. It has been known that these tumor associated immune cells may possess tumor-antagonizing or tumor-promoting functions. Although the tumor-antagonizing immune cells within TME tend to target and kill the cancer cells in the early stage of tumorigenesis, the cancer cells seems to eventually escape from immune surveillance and even inhibit the cytotoxic function of tumor-antagonizing immune cells through a variety of mechanisms. The immune evasion capability, as a new hallmark of cancer, accidently provides opportunities for new strategies of cancer therapy, namely harnessing the immune cells to battle the cancer cells. Recently, the administrations of immune checkpoint modulators (represented by anti-CTLA4 and anti-PD antibodies) and adoptive immune cells (represented by CAR-T) have exhibited unexpected antitumor effect in multiple types of cancer, bringing a new era for cancer therapy. Here, we review the biological functions of immune cells within TME and their roles in cancer immunotherapy, and discuss the perspectives of the basic studies for improving the effectiveness of the clinical use. •The biological functions of the immune cells within the tumor microenvironment.•The roles of the immune cells in cancer immunotherapy.•The perspectives of the basic studies for improving the effectiveness of the clinical use.